2013
DOI: 10.1093/cercor/bht276
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Planning Performance from Structural Connectivity Between Left and Right Mid-Dorsolateral Prefrontal Cortex: Moderating Effects of Age During Postadolescence and Midadulthood

Abstract: Complex cognitive abilities such as planning are known to critically rely on activity of bilateral mid-dorsolateral prefrontal cortex (mid-dlPFC). However, the functional relevance of the structural connectivity between left and right mid-dlPFC is yet unknown. Here, we applied global tractography to derive streamline counts as estimates of the structural connectivity between mid-dlPFC homologs and related it to planning performance in the Tower of London task across early to midadulthood, assuming a moderating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
3
10
0
Order By: Relevance
“…Consistent with previous research, our findings provide further support for the influential role of the right hemisphere in pain processing (Coghill et al, 2001;Symonds et al, 2006), and for the role of interhemispheric connectivity in maintaining functional hemispheric asymmetries (Kaller et al, 2015). Furthermore, the DLPFC has been implicated in the processes of monitoring and manipulating information, and working memory in the context of pain processing (Craggs et al, 2007).…”
Section: Regression Analysessupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous research, our findings provide further support for the influential role of the right hemisphere in pain processing (Coghill et al, 2001;Symonds et al, 2006), and for the role of interhemispheric connectivity in maintaining functional hemispheric asymmetries (Kaller et al, 2015). Furthermore, the DLPFC has been implicated in the processes of monitoring and manipulating information, and working memory in the context of pain processing (Craggs et al, 2007).…”
Section: Regression Analysessupporting
confidence: 90%
“…Likewise, Kaller et al (2015), indicated that structural, transcallosal DLPFC pathways appear to maintain hemispheric functional asymmetries. These authors also found that individual differences in DLPFC-DLPFC structural connectivity relate to differences in cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, our results support the findings of McRae et al (2012a,b), who did not find significant associations of general reappraisal ability with response inhibition, but with WM capacity (McRae et al, 2012b). Therefore, our results revealed that REAPPself might not be dependent only on dACC and inhibition, but also on WM process and strategy planning functions that rely on dlPFC areas (Heyder et al, 2004; Kaller et al, 2011, 2013). …”
Section: Discussionmentioning
confidence: 65%
“…One study manipulated the two independent parameters of planning in an event‐related fMRI study using the Tower of London task and revealed a double dissociation as indicated by a significant crossover interaction of hemisphere and task parameters . Another study demonstrated that the strength of mid‐DLPFC connectivity was critical in predicting individual differences in planning performance in the Tower of London test at various stages of adulthood . Furthermore, heroin‐dependent subjects have been reported to perform poorly in the Tower of London test and exhibit poor executive function .…”
Section: Discussionmentioning
confidence: 99%